2017
DOI: 10.3389/fnmol.2017.00024
|View full text |Cite
|
Sign up to set email alerts
|

Redundant Postsynaptic Functions of SynCAMs 1–3 during Synapse Formation

Abstract: Investigating the roles of synaptogenic adhesion molecules during synapse formation has proven challenging, often due to compensatory functions between additional family members. The synaptic cell adhesion molecules 1–3 (SynCAM1–3) are expressed both pre- and postsynaptically, share highly homologous domains and are synaptogenic when ectopically presented to neurons; yet their endogenous functions during synaptogenesis are unclear. Here we report that SynCAM1–3 are functionally redundant and collectively neces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 44 publications
0
10
1
Order By: Relevance
“…Thus, Cadm1b might have distinct signaling and adhesion-based functions in myelin sheath growth. Although we did not find evidence that disruption of Cadm1b function alters presynaptic assembly, as manifested by axonal vesicle clustering, multiple transsynaptic adhesion systems are thought to operate in parallel at synapses 60,61 , and redundancy within and between families can obscure how individual adhesion proteins contribute to synapse formation. Intriguingly, oligodendrocyte expression of a Cadm4 variant, a protein with structural similarity to Cadm1b, consisting of the extracellular and transmembrane domains, predicted to promote adhesion, resulted in a large excess of short sheaths 62 .…”
Section: Discussioncontrasting
confidence: 73%
“…Thus, Cadm1b might have distinct signaling and adhesion-based functions in myelin sheath growth. Although we did not find evidence that disruption of Cadm1b function alters presynaptic assembly, as manifested by axonal vesicle clustering, multiple transsynaptic adhesion systems are thought to operate in parallel at synapses 60,61 , and redundancy within and between families can obscure how individual adhesion proteins contribute to synapse formation. Intriguingly, oligodendrocyte expression of a Cadm4 variant, a protein with structural similarity to Cadm1b, consisting of the extracellular and transmembrane domains, predicted to promote adhesion, resulted in a large excess of short sheaths 62 .…”
Section: Discussioncontrasting
confidence: 73%
“…Cadm4 mediates internodal axoglial adhesion by binding to axonal Cadm2 and Cadm3 in both the peripheral (Maurel et al, 2007;Spiegel et al, 2007) and the central (Pellissier et al, 2007;Sharma et al, 2015; Figure S4A) nervous systems. However, in line with the presence of multiple members of this family in both neurons and myelinating glia and their combinatorial heterophilic binding properties, as well as their redundant function in other systems (Fowler et al, 2017), genetic deletion of individual Cadm genes in mice resulted in only marginal myelination phenotypes (Golan et al, 2013;Park et al, 2008;Zhu et al, 2013). By using a different experimental approach that relies on the expression of the extracellular domain of Cadm4 in OLs, we reveal a critical role for cell adhesion in myelin targeting, membrane wrapping, and lateral extension of the myelin sheath.…”
Section: Introductionmentioning
confidence: 94%
“…Inputs Studies in cultured neurons indicated redundancy between synaptic adhesion molecules of the SynCAM family (Fowler et al, 2017) and between neuroligins (Nlgns) and LRRTMs (Ko et al, 2011). These studies assessed the effect of combinatorial loss of postsynaptic adhesion proteins that bind to common presynaptic receptors (SynCAMs in the case of SynCAMs, Biederer et al, 2002;Nrxn for Nlgns and LRRTMs, Krueger et al, 2012), which might result in partial functional convergence.…”
Section: Context-dependent Effects Of Lrr Proteins At Ca1mentioning
confidence: 99%